Zarządzanie procesem budowy zintegrowanego sytemu informacji ubezpieczeniowej i jego organizacja na polskim rynku ubezpieczeniowym - Pazio, Nemezjusz M. (Organization and Management of the Integrated Process Insurance Information System in the Context of the Perspectives of the Polish Insurance Market, 2008)
The article describes some issues mainly connected with organizational aspects of creation data in the Polish motor insurance sector. In the framework of this article, selected problems and directions of steps taken towards the creation of insurance information system integrated in Poland have been presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 336-343